Finite element analysis and in vitro tests on endurance life and durability of composite bone substitutes - Seraji, Amir Abbas; Nahavandi, Reza; Kia, Amir; Rabbani Doost, Ahad; Keshavarz, Vahid; Sharifianjazi, Fariborz; Tavamaishvili, Ketevan; Makarem, Dorna (Frontiers in Bioengineering and Biotechnology, 2024)
Bone structures facilitate the regeneration and repair of bone tissue in regions where it has been damaged or destroyed, either temporarily or permanently. Therefore, the bone’s fatigue strength and durability are crucial to its efficacy and longevity. Several variables, such as the construct’s material qualities, design, and production procedure, loading and unloading cycles, and physiological conditions influence the endurance life of bone constructs. Metals, ceramics, and polymers are all routinely utilized to create bone substitutes, and each of these materials has unique features that might affect the fatigue strength and endurance life of the final product. The mechanical performance and capacity to promote bone tissue regeneration may be affected by the scaffold’s design, porosity, and pore size. Researchers employ mechanical testing under cyclic loading circumstances as one example of an experimental approach used to assess bone construction endurance. These analyses can give us important information about the stress-strain behavior, resistance to multiple loading cycles, and fatigue strength of the new structure. Predicting the endurance life of the developed construct may also be possible with the use of simulations and numerical analyses. Hence, in order to create reliable and efficient constructs for bone tissue engineering, it is crucial to understand their fatigue strength and durability. The purpose of this study is to analyze the effective parameters for fatigue strength of bone structures and to gather the models and evaluations utilized in endurance life assessments.